2014
DOI: 10.1523/jneurosci.1149-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Regulation of AMPA Receptor Trafficking

Abstract: Gangliosides are major cell-surface determinants on all vertebrate neurons. Human congenital disorders of ganglioside biosynthesis invariably result in intellectual disability and are often associated with intractable seizures. To probe the mechanisms of ganglioside functions, affinity-captured ganglioside-binding proteins from rat cerebellar granule neurons were identified by quantitative proteomic mass spectrometry. Of the six proteins that bound selectively to the major brain ganglioside GT1b (GT1b:GM1 Ͼ 4;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 55 publications
(1 reference statement)
3
30
0
Order By: Relevance
“…These results indicate that ceramide is not modulating AMPAR expression itself but might be necessary for other mechanisms in spinogenesis. In fact, other studies have described the involvement of GM1 ganglioside (a ceramide derivative) in the regulation of GluA2-containing AMPAR synaptic content by acting on endocytosis (46). In summary, our results demonstrate that CPT1C is necessary for an efficient translation of AMPARs.…”
Section: Cpt1csupporting
confidence: 69%
“…These results indicate that ceramide is not modulating AMPAR expression itself but might be necessary for other mechanisms in spinogenesis. In fact, other studies have described the involvement of GM1 ganglioside (a ceramide derivative) in the regulation of GluA2-containing AMPAR synaptic content by acting on endocytosis (46). In summary, our results demonstrate that CPT1C is necessary for an efficient translation of AMPARs.…”
Section: Cpt1csupporting
confidence: 69%
“…It has been reported that the activation of AMPA receptors increases the expression of several isoforms of gangliosides in the hippocampus [ 24 ]. Gangliosides have the ability to regulate the function of the AMPA receptor [ 25 ]. Similarly, the association between phospholipids and glutamate trafficking has also been reported, for example the ability of phosphatidylinositol in maintaining glutamate synaptic trafficking [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An unbiased screen for nerve cell proteins that differentially bind to gangliosides GT1b and GM1 revealed a group of proteins that regulate the intracellular trafficking of the GluR2 subunit of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) type glutamate receptor, the major excitatory neurotransmitter receptor in the brain [75]. AMPA receptors are tetrameric transmembrane proteins composed of dimers of dimers constructed from four gene products (GluR1-GluR4), the most common being GluR1-GluR2 and GluR2-GluR3 [76].…”
Section: Functions Of Nervous System Gangliosides In Health and Diseasementioning
confidence: 99%